Becoming teachers of inner-city students : life histories and teacher stories of committed White teachers - Jupp, James C. (Studies in inclusive education (Sense Publishers), 2013)
Becoming Teachers of Inner-city Students takes on the continuing challenges of White teachers in increasingly de facto re-segregated schools of the present. Drawing on the author's eighteen years of experience as a classroom teacher and his research on White teachers of inner-city students, Becoming Teachers provides key discussions on professional identity for preservice teachers, professional educators, and researchers interested in diversity education or urban education. Driving at complex recognitions of race, class, culture, language, and gender as a basis for teaching and learning with d.